Structural performance optimization of Reinforced concrete buildings with rooftop Telecommunication towers: A location-based analysis - Ojha, Bimal; Sabin Khatri; Prabin Pokharel; Rasique Jirel; Binay Jamarkattel; Abhinesh Khatri (Journal of Innovations in Engineering Education, 2024)
This study evaluates the structural response of an RCC building in Parbat, Nepal, with a rooftop telecommunication tower positioned at various locations. In our case, a telecommunication tower is already located at a certain position in the building, and we are trying to evaluate the optimal position of telecommunication tower. The site lies in seismic Zone V as per IS 1893:2016 (Part 1), indicating very high seismic activity, and is subject to significant wind loads. This study examines the structural response of an RCC building with a rooftop telecommunication tower, using ETABS 18.1.1 and adhering to IS 1893:2016 (Part 1) seismic design standards. The analysis focuses on the impact of tower placement on critical structural parameters, such as base shear, nodal displacement, axial and shear forces, and bending and torsional moments. Through five tower placement scenarios, the study highlights significant findings: a 2.37% increase in base shear, up to 9.86% variation in axial forces, and a maximum 26.60% change in shear forces. By isolating tower location as a variable, this research provides detailed insights into how tower positioning affects building performance. A finite element analysis approach is used, ensuring accuracy by explicitly modeling RCC-steel tower interactions and bolted connection of telecommunication tower and RCC structure.